Nonpolynomial numerical scheme for fourth-order fractional sub-diffusion equations - Li, Xuhao (2018)
We shall develop a high order numerical scheme for a fourth-order fractional sub-diffusion problem. Theoretical results will be established in maximum norm and it is shown that the convergence order is higher than some earlier work done. Numerical experiments will be carried out to demonstrate the efficiency of the proposed scheme as well as to compare with other methods.